2012
DOI: 10.3389/fncom.2012.00083
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of dendritic delay in octopus cells of the mammalian cochlear nucleus

Abstract: Octopus cells, located in the mammalian auditory brainstem, receive their excitatory synaptic input exclusively from auditory nerve fibers (ANFs). They respond with accurately timed spikes but are broadly tuned for sound frequency. Since the representation of information in the auditory nerve is well understood, it is possible to pose a number of questions about the relationship between the intrinsic electrophysiology, dendritic morphology, synaptic connectivity, and the ultimate functional role of octopus cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…The rate of change of the membrane voltage is calculated over one time step (10 μs ), and a spike is initiated when this value exceeds a threshold. This is a simplification of previous detailed modelling work [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The rate of change of the membrane voltage is calculated over one time step (10 μs ), and a spike is initiated when this value exceeds a threshold. This is a simplification of previous detailed modelling work [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…We model onset behaviour abstractly as the weighted difference of two low-pass filtered signals (with different time constants). This can be interpreted either as two precisely timed excitatory/inhibitory pathways, or in a similar way to the octopus cell model of Spencer et al (2012Spencer et al ( , 2018 and Ferragamo and Oertel (2002). Their model uses a spike threshold on the rate of change of the membrane potential Brette, 2010, 2011), which we reformulated in terms of firing rates (see Methods and Appendix).…”
Section: Onset and Adaptation Mechanisms Can Explain Rising Slope Prementioning
confidence: 99%
“…The compression and gain mechanisms did not contribute substantially ( Figure 3A). We investigated the octopus cell model discussed earlier (Ferragamo and Oertel, 2002;Spencer et al, 2012Spencer et al, , 2018 and found that it could provide a good fit only if adaptation was present alongside the onset mechanism ( Figure 3AD). For model variants including the onset mechanism, the positive or excitatory time constant τ e must be small (Figures 2A and 4B), and the negative or inhibitory time constant τ i must be larger than τ e ( Figure 3CD, τ e versus τ i ).…”
Section: Mechanisms Are Highly Robustmentioning
confidence: 99%
See 2 more Smart Citations